Edukasi Pentingnya Gizi Seimbang pada Remaja di SMPN 23 Kota Serang - Zahrah, Nisri Ina; Selvianita, Defi; Qonita, Qonita; Yulvia, Novrita Tri; Lestari, Puji (Jurnal Abdimas Kesehatan (JAK), 2024)
Growth and development enhancement during adolescence is the reason for the increased nutritional needs of adolescents. Lack of educational exposure related to nutrition is a trigger for unhealthy food choices. This education aims to provide education to increase understanding of the importance of balanced nutrition in adolescents. The education was held in September 2023 at SMPN 23 Serang City involving 150 students. Education is given through active lecture and question-answer methods using PowerPoint media. The results of the evaluation were measured by giving several questions related to balanced nutrition before and after present the education. Students can explain the composition and distribution of portions on one dinner plate and can mention the distribution of nutritionally balanced food portions in one day. It can be concluded that education using PowerPoint media for adolescents is effective in increasing students' knowledge about the importance of balanced nutrition